Urban Development Resource Conservation and Water Sustainability - Santhosh, Ar. Beena (Novel Perspectives of Geography, Environment and Earth Sciences Vol. 1, 2022)
We have come a long way in defining and understanding "sustainability," from the Brundtland Commission report being tabled in 1987 to the UN Sustainable Development Goals 2030. The UN SDGs are a road map for achieving long-term growth for people and the planet. The Earth's resources are being depleted faster than ever before, but technological advances in various fields have raised our awareness and knowledge of how to mitigate the adverse effects. Globally, it is critical to gain citizens' support in order to achieve environmental, social, and economic sustainability for all stakeholders. This is a case study paper, and while all aspects of a liveable city, such as safety, wellbeing, security, and infrastructure, are necessary for any city to function effectively, the paper's focus is on water sustainability. From floods in Kerala to drought in Vidarbha and Chennai running out of potable drinking water, the climate change crisis is indicating that water sustainability through integration of the water cycle is essential. Rotterdam, Denmark, is a city that has taken steps to make itself more resilient, sustainable, and livable. Water is incorporated into Dutch city planning, and community participation is encouraged through waterfront development and community welfare activities. The current paper examines one such effort by Navi Mumbai Municipal Corporation, which has incorporated the Dutch Model of water management by constructing holding ponds. The importance and application of Bio-Swales are also thoroughly explained. Participatory planning and implementation will aid cities in becoming more livable and sustainable.